Roosting behavior of Rousettusamplexicaudatus (Linn.) in Monfort Bat Cave, Island Garden City of Samal. - Navarro, Alfred Daniel, M. (2010)
Geoffrey's rousette (Rousettus amplexicaudatus) is one of the most common flying foxes in South East Asia. Roosting behavior of R. amplexicaudatus was investigated at Monfort Bat Conservation Park in the Isaland Garden City of Samal, where the largest colony of this species of megabats is found. Behavioral units of R. amplexiacudatus were identified, described, and categorized as either general maintenace behavior or social behavior. the activities of these flying foxes were sampled using the Istantaneous Sampling Method. Sleeping had the highest mean percentage, 76.24%, among all behavioral activities observed during the bats' stay in their roost site. Sleeping was followed by resting, with a mean percentage of 11.91%Grooming ranks third having a mean percentage of 3.67%. followed by stretching 1.91%, flight (1.35%), locomotion (0.82%) yawning (0.073% ) defecating (0.021%) and the general maintenace behavior with the least mean percentage was urinating (0.008%). Among social behavior, courting had the highest mean percentage, 0.16%, followed by aggresion, 0.14%.Copulation had the least mean percentage with a value of 0.008%. the duration of sleeping, resting, flight, locomotion yawning, stretching and aggression of R. amplexicaudatus in a day appear to be affected by weatherconditins or difference in temperature between months. with other behavioral activities, like grooming, defecating and urinating, there is no significant difference in duration between different sampling periods as these activities are required at similar amounts of time througout the year and is therefore not affected by season. Courting and copulation are behaviral activities that are highly dependent on the reproductive conditins of individuals.